2014
DOI: 10.15252/emmm.201303783
|View full text |Cite
|
Sign up to set email alerts
|

Gain‐of‐function mutation in TASK‐4 channels and severe cardiac conduction disorder

Abstract: Analyzing a patient with progressive and severe cardiac conduction disorder combined with idiopathic ventricular fibrillation (IVF), we identified a splice site mutation in the sodium channel gene SCN5A. Due to the severe phenotype, we performed whole-exome sequencing (WES) and identified an additional mutation in the KCNK17 gene encoding the K2P potassium channel TASK-4. The heterozygous change (c.262G>A) resulted in the p.Gly88Arg mutation in the first extracellular pore loop. Mutant TASK-4 channels generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
68
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 59 publications
1
68
0
Order By: Relevance
“…NaCl, 5 mM KCl, 1 mM CaCl 2 , 1 mM MgCl 2 , 0.33 mM NaH 2 PO 4 , 10 mM glucose, 2 mM sodium pyruvate, and 5 mM HEPES (pH 7.4 with NaOH) as previously described (49,50). Patch-clamp experiments were performed in the whole-cell configuration using pipettes pulled from borosilicate glass capillaries.…”
Section: Wesmentioning
confidence: 99%
See 1 more Smart Citation
“…NaCl, 5 mM KCl, 1 mM CaCl 2 , 1 mM MgCl 2 , 0.33 mM NaH 2 PO 4 , 10 mM glucose, 2 mM sodium pyruvate, and 5 mM HEPES (pH 7.4 with NaOH) as previously described (49,50). Patch-clamp experiments were performed in the whole-cell configuration using pipettes pulled from borosilicate glass capillaries.…”
Section: Wesmentioning
confidence: 99%
“…Data analysis of action potentials was done using Fitmaster software (HEKA). For each cell measured, the action potential parameters were averaged by analyzing 10 subsequent action potentials, as previously described (49).…”
Section: Wesmentioning
confidence: 99%
“…Furthermore, classic efforts to link genes to Mendelian disease are gradually being displaced by next-generation sequencing platforms (23)(24)(25), and exome sequencing has proved itself as an indispensable technology to identify disease-causing coding variants in congenital arrhythmia syndromes (26,27). Thus, we used a strategy seeking to identify gene variants affecting either ion channels, associated channel proteins, or loci associated with QT interval variability that could explain variable expressivity in an LQT2 family.…”
Section: Introductionmentioning
confidence: 99%
“…However, a wealth of transgenic animal studies support the notion that TASK family K 2p channels also strongly contribute to cardiac repolarization (30)(31)(32). Recently, Friedrich et al (27) used exome sequencing to identify a gain-of-function mutation in KCNK17 that in tandem with an SCN5A mutation underpinned the molecular mechanism of a severely affected arrhythmia phenotype. Furthermore, work by Schmidt et al (33) showed that pharmacological inhibition of a K 2p (TASK-1) is a novel potential pharmacological strategy for treatment of chronic atrial fibrillation.…”
Section: Introductionmentioning
confidence: 99%
“…WIK-related cid-ensitive + (TASK) channels belonging to the K 2P family of potassium channels are relevant for the pathogenesis of many different cardiovascular diseases [1, 2], including pulmonary hypertension [3], obstructive sleep apnea [4] and arrhythmias like atrial fibrillation (AFib) [4-6] or conduction disorders [7, 8]. …”
Section: Introductionmentioning
confidence: 99%